PENINGKATAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGUNAKAN METODE PROBLEM BASED LEARNING MATA PELAJARAN PENDIDIKAN AGAMA ISLAM-BUDI PEKERTI - Dewi Mahbubah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education and Ethics (PAI-BP) by applying the Problem-Based Learning (PBL) method. The focus of the material is on worship, including the eclipse prayer, istisqa prayer, and funeral prayer. This research was conducted in class VIII E at SMP Negeri 1 Tanjunganom during the odd semester of the 2024/2025 academic year, involving 32 students. The study employed a Classroom Action Research (CAR) design, consisting of two cycles, each comprising the stages of planning, implementation, observation, and reflection. The results indicated that the implementation of the PBL method significantly improved student learning outcomes, as evidenced by the increase in the class average score and the percentage of mastery from the pre-cycle to the first and second cycles. PBL also enhanced students' active participation in the learning process. Therefore, the PBL method is effective in improving learning outcomes on worship-related topics in the PAI-BP subject.